2019
DOI: 10.1021/acs.est.8b06720
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Stress Responses to Copper and Arsenic in a Field Population of Daphnia

Abstract: Over the past decade, significant advances have been made to unravel molecular mechanisms of stress response in different ecotoxicological model species. Within this study, we focus on population level transcriptomic responses of a natural population of Daphnia magna Straus, (1820), to heavy metals. We aim to characterize the population level transcriptomic responses, which include standing genetic variation, and improve our understanding on how populations respond to environmental stress at a molecular level.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…Notably, while the interaction type for mortality was additive or synergistic based on the chlorpyrifos concentration in the companion study (Delnat et al., 2019), the interaction type at the gene expression level also showed antagonistic interaction effects next to additive and synergistic interaction effects. Differences in interaction types between life history traits and gene expression levels were also documented in the water flea ( Daphnia magna , Straus 1820) where the combined exposure to arsenic and copper caused an antagonistic interaction effect on reproduction while there was also a synergistic interaction effect at the level of gene expression (Asselman et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, while the interaction type for mortality was additive or synergistic based on the chlorpyrifos concentration in the companion study (Delnat et al., 2019), the interaction type at the gene expression level also showed antagonistic interaction effects next to additive and synergistic interaction effects. Differences in interaction types between life history traits and gene expression levels were also documented in the water flea ( Daphnia magna , Straus 1820) where the combined exposure to arsenic and copper caused an antagonistic interaction effect on reproduction while there was also a synergistic interaction effect at the level of gene expression (Asselman et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Larvae were collected 2 hr after the last pulse application to ensure exposure to the desired chlorpyrifos concentration at the moment of sampling. This is important because gene expression can vary strongly over time (Asselman et al., 2019; Jovic et al., 2017). Note that any stress caused by the renewal was also present in the control.…”
Section: Methodsmentioning
confidence: 99%
“…Many reports have focused on the physiological characteristics of crops under Cu stress. Excessive Cu inhibits plant growth and induces ROS production, which subsequently damages plant cells [47][48][49][50].…”
Section: Discussionmentioning
confidence: 99%
“…An array was designed to analyse the transcriptional changes of 40 genes, and five endogenous references – primer sequences and their efficiencies can be found in the Supplementary Table S1, and efficiencies were calculated according to Ozáez et al [ 50 ]. The set of 40 genes was rationally selected considering their established/putative involvement in the biological functions affected by Cu toxicity or mechanisms underpinning detoxification pathways and stress responses of invertebrates facing metal contamination [ 10 , 33 , 51 ]. The selection and its rationale are detailed in Supplementary Section S2.…”
Section: Materials E Methodsmentioning
confidence: 99%
“…Regarding freshwater biota, the crustacean Daphnia magna is a model organism in ecotoxicology, being widely considered in regulatory frameworks and recognized as a model invertebrate for environmental omics research [ 30–32 ]. While the molecular mechanisms of tolerance to copper remain fairly unexplored in Daphnia , previous studies demonstrated the capacity of this metal to modulate gene expression and promote epigenetic changes in a manner related to the history of exposure, and that such alterations supported known and uncovered novel mechanisms of metal toxicity [ 10 , 33 , 34 ]. Furthermore, it has been suggested that metals can potentially influence the gene expression profiles of non-exposed offspring, though this has never been experimentally confirmed for daphnids [ 35–37 ].…”
Section: Introductionmentioning
confidence: 99%